Housing Policy in Developing Countries : The Importance of the Informal Economy - Arnott, Richard (World Bank, Washington, DC, 2017)
All countries have a formal economy and an informal economy. But, on average, in developing countries the relative size of the informal sector is considerably larger than in developed countries. This paper argues that this has important implications for housing policy in developing countries. That most poor households derive their income from informal employment effectively precludes income-contingent transfers as a method of redistribution. Also, holding fixed real economic activity, the larger is the relative size of the informal sector, the lower is fiscal capacity, and the more distortionary is government provision of a given level of goods and services, which restricts the desirable scale and scope of government policy. For the same reasons, housing policies that have proven successful in developed countries may not be successful when employed in developing countries.